How much physiology do fourth year nursing students really remember? - Purani, Sharlini; Narnaware, Yuwaraj; Neumeier, Melanie; Cuschieri, Sarah; Chahal, Paul (My University, 2024)
There is a growing concern that nursing students struggle to retain adequate physiological knowledge throughout their program to meet their entry to practice competencies. However, how much and when this knowledge is lost over a four-year undergraduate Bachelor of Science in Nursing program is yet to be evaluated. According to Narnaware Y. 2021, physiological knowledge retention has yet to be studied as comprehensively as anatomical knowledge retention in healthcare disciplines, including nursing programs. This study aims to assess the extent of physiological knowledge decline among nursing students by their fourth year. It is evaluated by comparing their understanding of physiological knowledge in the first year after their physiology course and the fourth year after completing their Critical Care nursing course. Physiological knowledge loss was assessed in fourth-year nursing students by quizzing them on ten organ systems using the online quizzing platform – Kahoot. About nine to eleven knowledge and comprehension-level multiple-choice questions were delivered. These scores were then compared to first-year quiz scores on the same content to determine overall knowledge loss over three years. The data was analyzed by using SPSS II and compared using 2-sample t-tests. The findings of this research illustrate a general reduction in knowledge loss, with variations in the decline specific to each system. In medical and allied health students, the knowledge loss was significantly lower than previously reported (Pourshanazari et al., 2013). Compared to the third year, knowledge loss in the fourth year, however, is not significantly different (Narnaware et al., 2021).
Presented on April 19, 2024, at Student Research Day held at MacEwan University in Edmonton, Alberta, Canada, and May 25-29, 2024 at the Human Anatomy and Physiology Society (HAPS) Annual Conference held at The Marriott St. Louis Grand in St. Louis, Missouri, United States.
Keywords: knowledge retention; nursing students